PENGUKURAN KINERJA KEUANGAN PADA PEMERINTAH DAERAH (Studi Kasus di Kabupaten Kotawaringin Timur) - Priola Meilida; Aris Eddy Sarwono; Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the performance of the East Kotawaringin Regency government. This research was conducted at the local government of East Kotawaringin Regency. The type of data used is secondary data.The results of this study address the financial ratios of the decentralization rate of 11.60% in the very low category. The independence ratio of 11.60% falls into the very low category with an Instructive relationship pattern. The dependent ratio is 72.15% in the medium category. The effective ratio of 115.43% belongs to the effective category. An efficient ratio of 90.38% is included in the less efficient category. The growth ratio of 24.34% is in the medium category. The financial performance of the local government of East Kotawaringin Regency can be accessed well when compared to the Districts and Cities in Central Kalimantan Province together with West Kotawaringin and Palangkaraya Districts.